Summary of Experience in Geological Investigation of Nepal Hydropower Station - DING Bin; PEI Xiaodong; XU Kaikai (Renmin Zhujiang)
With the advancement of "The Belt and Road", hydropower development is an important strategic measure of the Nepalese government. Nepal has complex regional structure and geological condition. Based on the engineering experience of several hydropower stations in Nepal, this paper summarizes the key points of the geological investigation of Nepal hydropower station. As the main method of geological investigation in Nepal, geological mapping can analyze the main geological problems of the project. With the method of combining geological observation point and UAV technology, the geological information of the engineering area from macro to micro can be obtained, and the work efficiency and accuracy of geological mapping can be improved. The deep overburden is the key and difficult point of the geological investigation of Nepal hydropower station. To find out geological problems of deep overburden, a variety of investigation methods are required. In the deep overburden exploration, mud and SM natural plant gum are used as the drilling fluid and SD single-acting double-tube two halves tube drilling tool is used for rotary drilling, which can effectively improve the core recovery percent and work efficiency. The engineering experience summarized in this paper is worth for geological investigation of similar projects in Nepal as reference.